Light-Fidelity as Next Generation Network Technology: A Bibliometric Survey and Analysis - Safitri, Cutifa; Galina, Mia; Simatupang, Joni Welman (Universitas Muhammadiyah Malang, 2022)
This paper delivers a systematic review and a bibliometric survey analysis of Light-Fidelity (Li-Fi) indoor implementation in Next Generation Network (NGN). The main objective of this study is to design a communication network based on NGN-Li-Fi for the indoor implementation which aims to increase user Quality of Service (QoS). The main merits and contributions of this study are the thorough and detailed analysis of the review, both in literature surveys and bibliometric analysis, as well as the discussion of the implementation model challenges of Li-Fi in both indoor and outdoor environments. The issue articulated in an indoor communication network is the possibility of intermittent connectivity due to barriers caused by line-of-sight (LOS) between the LED transmitter and receiver, handover due to channel overlap, and other network reliability issues. To realize the full potential and significant benefits of the Next Generation Network, challenges in indoor communication such as load-balancing and anticipating network congestion (traffic congestion) must be addressed. The main benefit of this study is the in-depth investigation of surveys in both selected critical literatures and bibliometric approach. This study seeks to comprehend the implications of Next Generation networks for indoor communication networks, particularly for visible light communication channels.